Rapid Sequence Intubation pada Pasien Hamil Ektopik dengan COVID-19 Ringan yang Menjalani Laparotomi Histerektomi - Wisudarti, Calcarina Fitriani Retno; Adiyanto, Bowo; Naomi, Diah Anis (Jurnal Komplikasi Anestesi, 2021)
Female patient aged 27 years was diagnosed with ectopic pregnancy in ampulla vateri, grade II hemorrhagic shock resolved, G2P1A0 8 weeks 5 days pregnant, mild COVID-19, underwent exploratory laparotomy and hysterectomy. The patient did not have any complaints of fever, cough, shortness of breath, and anosmia. The patient was diagnosed with mild COVID-19 because of a positive SARS-CoV-2 Qualitative PCR swab and no pneumonia. The operation was carried out in a special operation room for airborne infection patients with a HEPA filter machine installed. General anesthesia intubation using the RSI technique. No difficult airway was found in the patient. No Sellick maneuver was performed. Patient was intubated with a direct laryngoscope. The ETT position was confirmed by capnograph. After the operation, the patient was extubated deeply, then returned to the ward. There was no perioperative complication in this patient.